Hepatic myelolipoma in two Goeldi’s monkeys from South America held captive - Martins, Mariana Castilho [UNESP]; Rahal, Sheila Canevese [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Teixeira, Rodrigo Hidalgo Friciello; Teixeira, Carlos Roberto [UNESP]; Sequeira, Júlio Lopes [UNESP]; Nóbrega, Juliano [UNESP] (Wiley, 2016)
Two cases of hepatic myelolipoma in Goeldi's monkeys from South America are described. One was a female evaluated due progressive abdominal distension. Ultrasound and computed tomography detected hepatic mass. Partial hepatectomy was performed, but the monkey died after surgery. Case 2 was a male that died suddenly, showing non-specific clinical signs.
Keywords: computed tomography; Neotropical; primate; tumor